The hole story - Bright, Paul 1949- (Andersen Press, 2016)
Hamish and Hermione Hole need a new home but wherever they go they cause chaos. Will the two holes ever find a place where they are appreciated?
Keywords: Holes / Juvenile fiction; Children's stories / Pictorial works; Children's stories; Holes; Fiction; Juvenile works; Pictorial works; Children's picture books; Bilderbuch